RANCANG BANGUN APLIKASI SISTEM PENDUKUNG KEPUTUSAN PENENTUAN SUPPLIER OBAT TERBAIK MENGGUNAKAN METODE WEIGHTED PRODUCT PADA RUMAH SAKIT IBU DAN ANAK PUTRI SURABAYA - oktorianto, kevin widoni; Jusak, Jusak; Sudarmaningtyas, Pantjawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
Rumah Sakit Ibu dan Anak Putri Surabaya is located at Jalan Arief Rachman Hakim No. 122, Whiteness. Sukolilo Sub-district, Surabaya City. The agency is a type c hospital that moves in one type only in the field of mother and child service. The current process of drug purchase is done by looking at the criteria in terms of the cheapest price and the availability of goods on the part of suppliers so that the quality obtained is less satisfactory impact on the return of goods of 203 drugs from May to August. Therefore, the best drug supplier determination application using Weighted Product method has been made in this final project based on some additional criteria that have been used such as quantity criterion, price criteria, quality criteria, discount criteria, and delivery time criteria. In this application there are several functions consisting of purchase, acceptance and assessment. Where the company can reduce the return of drugs for the next period and the company can meet the needs of the required drugs. Based on the results of trials that have been made on the application of the determination of the best drug supplier can produce reports the best suppliers of drugs in accordance with the needs of the RSIA Putri Surabaya. This report is useful as management information in order not to do the return of drugs that occurred in the previous period. So the company can improve services and meet the needs of drugs needed by every part of the company.Keywords: Determination of Supplier, Weighted Product, criteria.